Pengaruh Audit Switching, Reputasi Audit dan Opini Audit terhadap Audit Delay - Utami, Fitri; Rusdi, Rusdi (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2025)
Audit delay, defined as the time lag between the fiscal year-end and the issuance date of the audit report, can undermine the timeliness and reliability of financial information for stakeholders. This study aims to examine the effect of audit switching, auditor reputation, and audit opinion on audit delay among property and real estate companies listed on the Indonesia Stock Exchange (IDX) from 2019 to 2023. Using a quantitative approach, the study applies panel data regression analysis on a purposive sample of 34 companies, resulting in 170 firm-year observations. The results reveal that audit switching has a statistically significant and positive effect on audit delay, indicating that a change of auditors tends to increase the time needed to complete audits. In contrast, auditor reputation and audit opinion do not significantly influence audit delay. Simultaneously, the three variables collectively have a significant impact on audit delay, although their overall explanatory power is low (Adjusted R² = 3.6%). These findings suggest that while audit switching should be managed carefully to avoid disruptions in reporting timelines, auditor reputation and audit opinion alone may not be sufficient predictors of audit completion time. Companies are advised to ensure proper coordination and documentation during auditor transitions to improve the efficiency of the audit process.